(3Jhbja GdMcGe Ydi ZhGeV GdCMcGes - (3CMeO Hf YeGO Hf jhSa Hf YHO GdfHj, CHh GdYHGS, TgGH GdOjf GdCbagSj Ke GdbGgQj , GHf GdpYneGO ,J (B808 (3g` s ((3YHOGdbGOQ Hf eMeO Hf s)
(3ChdgG (B:s
(3hHYO adeG cGf GdGfSGf bdjdkG HfaSg cKjQkG HCNjg s
(3BNQgG (B:s
(3hJhHI ef GdYHO Edi Gddg JYGdi hcJH Edjg GdWGYGJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B26s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg JjehQ (B219) s
Keywords: (3CUhd Gdabgs